(untitled) (The Agriculturists, 2012)
An attempt was made to develop sapota jam to assess its prospect in marketability. The fruits were collected from local market and the pulp was extracted in the laboratory. Then the pulp was analyzed monthly for proximate composition. The proximate analysis of sapota pulp showed moisture 70.07%, ascorbic acid 8.90 mg/100g, pH 5.10, TSS 19.4% and total sugar 16.07%. No special change of ingredients was found during two months of storage. But, a little change was observed after four months. The products (jam) with three different formulations (50%, 75% and 100% pulp of the standard formula) were prepared. Sodium benzoate was added as preservative in a required quantity. These products were packed in appropriate container. A taste panel consisting 10 panelists adjudged the acceptability of the samples. The consumers’ preferences were measured by statistical analysis. Among the samples, jam made with 75% pulp of the standard formula (sample A2) was adjudged the best product by the panelists. Keywords: Jam; sapota; ascorbic acid; sugar; Achras zapota DOI: http://dx.doi.org/10.3329/agric.v9i1-2.9473 The Agriculturists 2011; 9(1&2): 1-7